(untitled) (Journal of Patan Academy of Health Sciences, 2024)
Introduction: Nepal has made some progress in palliative care. Need for palliative care is more in rural areas where primary health care workers deliver most of the care. Their knowledge and attitude toward palliative care is very important to deliver the service in rural areas. This study aimed to assess knowledge and attitude of health workers working at health post level toward palliative care. Method: A cross-sectional descriptive study was carried out among 174 health workers working in health post of Makawanpur district. Census method was employed. Knowledge regarding palliative care was assessed by Palliative Care Knowledge Questionnaire-Basic (PCKQ-B), validated in India. Attitude related statements were adapted from previously conducted study in Palestine. Data were analyzed using descriptive statistics. Result: A total of 174 health workers participated in the study; 126(72.41%) were females, 70(40.23%) were between ages 20-30 years, 65(37.36%) had clinical experience of less than 5 years and majority were ANMs. Only 68(39.08%) had fair level of knowledge and 63(36.21%) had poor attitude. Majority of respondents had better understanding regarding basic knowledge of palliative care than pain management, morphine use and bereavement care. Most of the respondents showed unfavourable attitude toward caring for dying patient Conclusion: Primary health care workers have shown fair knowledge and poor attitude toward palliative care. This study emphasizes the need to introduce palliative care in the curriculum and training program of health workers to enhance their knowledge level and develop favourable attitude towards palliative care to better serve the rural population